Rapid, non-invasive fluorescence margin assessment: Optical specimen mapping in oral squamous cell carcinoma. (January 2019) - van Keulen, Stan; van den Berg, Nynke S.; Nishio, Naoki; Birkeland, Andrew; Zhou, Quan; Lu, Guolan; Wang, Han-Wei; Middendorf, Lyle; Forouzanfar, Tymour; Martin, Brock A.; Colevas, A. Dimitrios; Rosenthal, Eben L.
Highlights: Margins status assessment during surgery is highly complex. Optical specimen mapping (OSM) allows intraoperative whole specimen evaluation. OSM detects positive margins (<5 mm) with high sensitivity and specificity. OSM can guide pathological assessment of margins with frozen sectioning. Abstract: Objective: Surgical resection remains the primary treatment for the majority of solid tumors. Despite efforts to obtain wide margins, close or positive surgical margins (<5 mm) are found in 15–30% of head and neck cancer patients. Obtaining negative margins requires immediate, intraoperative feedback of margin status. To this end, we propose optical specimen mapping of resected tumor specimens immediately after removal. Materials and methods: A first-in-human pilot study was performed in patients (n = 8) after infusion of fluorescently labeled antibody, panitumumab-IRDye800 to allow surgical mapping of the tumor specimen. Patients underwent standard of care surgical resection for head and neck squamous cell carcinoma (HNSCC). Optical specimen mapping was performed on the primary tumor specimen and correlated with pathological findings after tissue processing. Results: Optical mapping of the specimen had a 95% sensitivity and 89% specificity to detect cancer within 5 mm (n = 160) of the cut surface. To detect tumor within 2 mm of the specimen surface, the sensitivity of optical specimen mapping was 100%. The maximal observed penetration depth of panitumumab-IRDye800 through human tissue in our study was 6.3 mm. Conclusion: Optical specimen mapping is a highly sensitive and specific method for evaluation of margins within <5 mm of the tumor mass in HNSCC specimens. This technology has potentially broad applications for ensuring adequate tumor resection and negative margins in head and neck cancers.